Resonant two-photon emission of an electron in the field of an electromagnetic wave - Voroshilo, O.I.; Roshchupkin, S.P. (Вопросы атомной науки и техники, 2007)
We present, for general relativistic case, a theoretical investigation of the resonant two-photon emission of an electron in the circularly-polarized electromagnetic wave. Resonances are related to a virtual intermediate particle that falls within mass shell. We find condition when resonances occur and we derive the expressions for the resonant amplitude and the differential probability when the invariant intensity of the wave is small ( η << 1 ). It is demonstrated that the resonant two-photon emission probability may be several orders magnitude greater than the probability of the corresponding process out of the resonance.